Mechanisms and regulation of the Hsp70 chaperone network - Wentink, Anne; Rosenzweig, Rina; Kampinga, Harm; Bukau, Bernd (Nature reviews, 2025)
The 70-kDa heat shock protein (Hsp70) chaperone is essential to maintain cellular protein homeostasis, facilitating the folding, assembly, membrane translocation and quality control of proteins. Hsp70s achieve their functions through ‘selective promiscuity’, interacting with a wide range of substrate proteins while minimizing undesired interactions. J-domain proteins (JDPs) and nucleotide exchange factors (NEFs) are key to substrate recognition, remodelling and release from chaperone complexes. JDPs either target Hsp70s to specific subcellular sites where substrates reside (recruiters) or bind substrates directly by using highly specific (specialists) or multiple, versatile (generalists) binding sites. Through diverse substrate-binding modes and regulatory mechanisms, the 50 human JDPs confer remarkable client specificity to Hsp70s, a function that is comparable to that achieved by close to 600 E3 ubiquitin ligases in targeting proteins for degradation. Moreover, JDPs, together with NEFs, dictate the fate of Hsp70 clients by directing them to distinct protein quality control pathways, resulting in their folding or degradation. These recent mechanistic insights into Hsp70 regulation not only highlight the versatility and complexity of the Hsp70 network but also offer new avenues for more specific interventions in ageing-related and other protein folding diseases.